PO231 A case of superficial siderosis mimicking myasthenia gravis. (1st December 2017) - Matthews, Rachael; Mirza, Farhat; Ramdass, Ranjit; Mohanraj, Rajiv
Abstract : Introduction: Superficial siderosis of the central nervous system (SSCNS) is caused by chronic subarachnoid haemorrhage. The clinical syndrome typically consists of sensorineural deafness, cerebellar ataxia, dementia and pyramidal tract signs. We describe a rare presentation of SSCNS mimicking myasthenia gravis. Case: A 56 year old gentleman, with childhood history of posterior fossa tumour resection, presented following a 10 year history of progressive hearing loss and development of slurred speech and difficulty swallowing, worse in the evenings. Examination demonstrated bilateral ptosis, diplopia on right horizontal gaze, bulbar dysarthria, spastic catch in the right upper limb and gait ataxia. Single fibre EMG revealed abnormal jitter in the orbicularis oculi, suggestive of a neuromuscular junction dysfunction. MR imaging of the brain showed typical changes of SSCNS. Blood tests for Ach receptor and MUSK antibodies were negative, and there was no clinical improvement with pyridostigmine. We concluded that the patients symptoms were exclusively due to SSCNS, and that the EMG changes occurred as a result of the facial nerve involvement. Discussion: This is the first reported case of SSCNS in the literature presenting with neuromuscular symptoms. The EMG findings in this provide further insights into the pathophysiology and the diagnosis of this rare condition.